Characterization of patients with chronic obstructive pulmonary diseases at the Intensive Care Unit - Alberto García Gómez (ECIMED, 2021)
Introduction: COPD is characterized by limitation of the airflow, progressive, partially reversible and associated to an abnormal inflammatory responsive of the lungs. Objective: To characterize patients with COPD admitted at the Intensive Care Unit. Methods: A descriptive, retrospective study was carried out in a series of 347 patients with chronic obstructive pulmonary disease admitted to intensive care. The variables age, sex, cause of admission, discharge status, APACHE II scale value at admission, invasive mechanical ventilation, tracheostomy, and direct cause of death according to autopsies performed were studied. Absolute and relative frequency distributions, measures of central tendency, and for comparison, the chi-square and Student's t tests were calculated, with a significance level of 5%. Results: The mean age was of 72,1 ± 8,2 years. The female sex (52.7%) and the age group of 60-79 years (67.1%) predominated. The female / male sex ratio was 1.1: 1.0. 64.8% of the patients were discharged dead. There were significant differences between the mean age of the deceased and the living (p = 0.001). The cause of clinical admission had the highest number of admissions (86.7%). The mean APACHE II value was higher in the deceased (21.0 vs. 15.2). 81.3% of the patients received mechanical ventilation, and 17.3% underwent a tracheostomy. The main cause of death was bacterial bronchopneumonia (67.2%). Conclusions: Patients with chronic obstructive pulmonary disease admitted to the intensive care unit have high mortality and it is associated with three main direct causes of death: bacterial bronchopneumonia, pulmonary thromboembolism and septic shock.